El Neuromarketing y la efectividad de las promociones en el sector comercial de Pucará en la ciudad de Riobamba. - Pino Chapalbay, Luis Miguel (2023)
The objective of this research work is to determine how Neuromarketing influences the effectiveness of promotions in the commercial sector of Pucará in the city of Riobamba. To comply with the above, a study was carried out that is based on the use of qualitative and quantitative methods, the data was collected through field observations and the application of a survey to 381 consumers. With this, it was possible to measure the degree of influence and interest obtained by generating stimuli for customers through the different marketing strategies frequently used. The result that has been obtained is to be able to establish new promotion strategies for the commercial sector through the support of neuromarketing techniques, which concludes that it is of utmost importance to know the behavior of the brain of consumers when they are exposed to various advertisements and how they make decisions.